Antibiotic Prescribing By Family Physicians For Upper Respiratory Tract Infections - Zoutman, Dick E; Ford, Douglas B; Bassili, Assil R (International Journal of Infection Control, 2009)
Feedback, non-antibiotic drug recommendations, and patient factors were examined to develop ways to reduce use of inappropriate antibiotics for Upper Respiratory Tract infections (URTIs). 3,220 encounters for URTIs over six months were reported by 45 family physicians who recorded consecutive patients and noted drugs recommended, diagnosis, and patient characteristics. After two months baseline data collection, physicians received feedback about their own and peers antibiotic prescribing, and the effect of this on their prescriptions was studied.Patients recommended ‘over the counter drugs’ were less likely to be given antibiotics for acute bronchitis (OR, 0.22; 95% CI, 0.13-0.38; P<0.0001), pharyngitis (OR, 0.46; 95% CI, 0.29-0.75; P=0.0001), acute sinusitis (OR, 0.08; 95% CI, 0.03-0.22; P<0.0001), and acute otitis media (AOM) (OR, 0.27; 95% CI, 0.11-0.65; P=0.004). Prescriptions for drugs other than antibiotics were also negatively associated with antibiotics for acute bronchitis (OR, 0.49; 95% CI, 0.31-0.78; P=0.003) and acute sinusitis (OR, 0.29; 95% CI, 0.12-0.72; P=0.007). Adults (OR, 1.8; 95% CI, 1.1-3.0;P=0.03), males (OR, 1.6; 95% CI, 1.0-2.5; P=0.05), and patients with co-morbidity (OR, 2.4; 95% CI, 1.4-4.0; P=0.001) were more likely to be prescribed antibiotics for acute bronchitis.After feedback antibiotic prescribing decreased from 42% to 34% of encounters (χ=16, p<0.0001) and use of the first choice antibiotics recommended in the Ontario guidelines increased from 45% to 56% (χ=10, p=0.002). The results suggest feedback would be an effective means to improve antibiotic prescribing, and recommendations of non-antibiotic therapies would lead to decreased antibiotic use.